MODEL MANAJEMEN PEMBELAJARAN ISLAM BERORIENTASI PADA PENGEMBANGAN LITERASI KEAGAMAAN ANAK USIA DINI - Eli Indriastuti; sunhaji (STKIP Subang, 2025)
This study aims to analyze the Islamic learning management model oriented toward developing religious literacy among early childhood learners at TK MNU Diponegoro 111 Ajibarang Kulon. This research employed a qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that learning planning was developed based on the principles of the Merdeka Curriculum and integrated Islamic values into the learning goals and activities, although the analysis of children’s learning needs was not yet conducted comprehensively. The implementation of learning was carried out through play-based activities, religious routines, and storytelling methods that provided concrete religious experiences for the children. Evaluation was conducted through observation and portfolios, but documentation was not consistently maintained. In conclusion, Islamic learning management at TK MNU Diponegoro 111 Ajibarang Kulon has been fairly effective in fostering religious literacy, although further improvement is needed in differentiation, individual needs assessment, and continuous evaluation to achieve more optimal learning outcomes. Keywords: Islamic Learning Management; Religious Literacy; Early Childhood; Merdeka Curriculum; TK MNU Diponegoro 111